Evaluation of Nigerian Gmelina arborea Seed Oil as a Sustainable Industrial Bio-resource (Unizik Journal of Chemical and Environmental Engineering, 2026)
A comprehensive characterization of Gmelina arborea seed oil was conducted to appraise its prospects as a sustainable industrial bioresource. The oil was extracted via Soxhlet method using n-hexane. Extraction at 60 °C for 50 minutes yielded 35.85% crude Gmelina arborea seed oil (GASO), light brown in color, with a specific gravity of 0.942. The characterization presented the oil with a kinematic viscosity of 75.813 mm2 s-1 at 40 °C, a refractive index of 1.4648 at 33 °C, and an acid value of 18.700 mg KOH/kg, corresponding to a free fatty acid value of 9.35 mgKOH/kg. The iodine value was 53.29 meq/100 g, the saponification value was 179.614 mgKOH/kg, and the molecular weight was 1045.90 g/mol.  Proximate analysis of the oil revealed ash content of 0.018% and moisture content of 0.287%, indicating high storage stability. These properties are closely aligned with those specified in ASTM D6751, suggesting that Gmelina arborea seed oil could serve as a non-edible substitute for conventional vegetable oils.  Gas Chromatography-Mass Spectrometry (GC-MS) analysis identified a robust fatty acid profile dominated by oleic acid (50.17%), n-hexadecanoic acid (19.20%), and octadecanoic acid (17.26%). The presence of high-value components such as squalene (1.18%) and beta-sitosterol (0.39%), which provide a balance between oxidative stability and low-temperature fluidity, further highlights the oil's multi-industrial potential. Fourier Transform Infrared (FTIR) spectroscopy confirmed the structural purity of the triacylglycerols, with a characteristic ester carbonyl (C=O) peak at 1742.5 cm-1 and a notable absence of oxidative degradation. FTIR also confirmed the presence of characteristic triglyceride ester linkages at 1745 cm-1. These results provide a fundamental baseline for developing Gmelina arborea seed oil based industrial feedstock, demonstrating that Gmelina arborea seeds which is presently regarded as residues can be transitioned from forest waste to a high-value and sustainable industrial bioresource
Keywords: Gmelina arborea; GC-MS; FTIR; Soxhlet Extraction; Bio- resource